Examination Committee Work Management System - Abdul Suleiman; Turfa Hamed; Nadia Saleh (Al-Rafidain Journal of Computer Sciences and Mathematics)
The aim of this paper is to design a software for examination committee work management using Visual FoxPro programming language, which is considered as one of the most popular and useful visual programming languages that supports Database Management System (DBMS). This software is designed to facilitate the management of examination committee work to assist the documentation for the important data like card files and records and to retrieve examination information. The software has the ability to display the students’ marks after data insertion. These data are gained from Microsoft Excel tables. In addition, the software could compute the annual total marks, the final marks, the average, and the estimation. Besides it could search the database for a specified student name. The students’ marks, the final results, and the sequence and estimation for passed students could be organized as a printing material. Also the software gives printed reports for first semester, midyear, second semester, and annual total marks, for all studied subjects of a specified stage and according to that stage classes. In addition to the capability of statistical computing for the pass ratio, total number of students and the number of passed students according to the stage, with printed capabilities.